For a Non-Fascist Didactics: questioning the training of teachers for the K-12 education - Samilo Takara; Teresa Kazuko Teruya (Universidade Federal do Rio Grande do Sul, 2015)
This article is about how the didactics in K-12 education can be thought through the notion of non-fascist life discussed by Michel Foucault (1991) when discussing the ways of life in the contemporary society. In Anti-Oedipus: Introduction to Non-Fascist Life, preface to the North American version of the work of Deleuze and Guattari, the author presents a time of instability and social, cultural and political changes. Our guiding question is: How can we use the didactics in contemporary times? Interested in thinking about education, we suggest the disintegration of a modern project of didactics in order to think about other possibilities in the work of teachers.